Intravenous iron for heart failure with evidence of iron deficiency: a meta-analysis of randomised trials - Graham, Fraser J. (Clin Res Cardiol, 2021)
BACKGROUND: The recent AFFIRM-AHF trial assessing the effect of intravenous (IV) iron on outcomes in patients hospitalised with worsening heart failure who had iron deficiency (ID) narrowly missed its primary efficacy endpoint of recurrent hospitalisations for heart failure (HHF) or cardiovascular (CV) death. We conducted a meta-analysis to determine whether these results were consistent with previous trials. METHODS: We searched for randomised trials of patients with heart failure investigating the effect of IV iron vs placebo/control groups that reported HHF and CV mortality from 1st January 2000 to 5th December 2020. Seven trials were identified and included in this analysis. A fixed effect model was applied to assess the effects of IV iron on the composite of first HHF or CV mortality and individual components of these. RESULTS: Altogether, 2,166 patients were included (n = 1168 assigned to IV iron; n = 998 assigned to control). IV iron reduced the composite of HHF or CV mortality substantially [OR 0.73; (95% confidence interval 0.59–0.90); p = 0.003]. Outcomes were consistent for the pooled trials prior to AFFIRM-AHF. Whereas first HHF were reduced substantially [OR 0.67; (0.54–0.85); p = 0.0007], the effect on CV mortality was uncertain but appeared smaller [OR 0.89; (0.66–1.21); p = 0.47]. CONCLUSION: Administration of IV iron to patients with heart failure and ID reduces the risk of the composite outcome of first heart failure hospitalisation or cardiovascular mortality, but this outcome may be driven predominantly by an effect on HHF. At least three more substantial trials of intravenous iron are underway. GRAPHIC ABSTRACT: [Image: see text] SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00392-021-01837-8.